استراتيجية توطين المناطق الاقتصادية الخاصة والمناطق الصناعية في الدول الناشئة: The strategy of localization for special economic zones & industrial zones In emerging countries - جميلة مداني (Journal of North African Economies, 2025)
The objective of the study is define the new strategy for special economics and industrial zones in emerging countries, facing the economic challenges, with a typical of industrial zones in the world, The study means a number of emerging countries, also which it included the Algerian strategy of industrial zones, We concluded in the study, a typical strategy to activate the industrial economic zones, which choose the best geographical zones, whose that facilitate the export of goods, so that the successes of emerging countries in activating industrial zones, by various mechanisms, the important of them is the foreign investment laws and legislations (tax reductions, equivalent quotas in exports), and control its by special administrative to coordinate the factors’ economic in the zones for Algeria and its prospects, the activation of the economic and industrial zones, has adopted policies and programs to rehabilitate the industrial zones.